'Un-sound' Sounds: Pornosonics of Female Desire in Indian Mediascapes. Issue 1 (July 2019) - Mini, Darshana Sreedhar
Abstract : Locating my study around a recent set of issues in India's mediascape, this article tracks the emergence of 'sonic publics' that are conditioned by the figure of the listener, her imaged aurality, and the aural tactics that are developed in response to censorship and a culture of redaction. In exploring the affective and embodied relationships forged through 'sonic publics', I trace the emergence of 'pornosonic' media that are held in a supplementary relationship with the pornographic, and their efficacy as a transactional medium where the work of sound is affective (working at the level of the body), social (working to create arrangements of public order around sonic artifacts) and cultural (filtered through cultural norms). Using the Hindi film Lipstick Under My Burkha (Dir. Alankita Srivastava, 2017), a phone-sex scandal in the Southern Indian state of Kerala, and the use of voiceover dubbing in the soft-porn industry as case studies, I argue that while these objects arguably exist as different 'genres' and operate at varying levels of 'offensiveness', they offer us ways of locating how sound becomes a site and object of contestation in the public sphere. This article is the winner of the 2018 Claudia Gorbman Writing prize awarded jointly by the SCMS Sound Studies SIG and the Music, Sound, and the Moving Image .